PENINGKATAN KEAKTIFAN PESERTA DIDIK KELAS X.1 SMA NEGERI 1 JAKENAN TAHUN AJARAN 2022/2024 DALAM PEMBELAJARAN SEJARAH MELALUI PEMBELAJARAN DEBAT AKTIF - Vajar Rizki Pratama (Universitas Negeri Semarang, 2024)
This research aims to improve the learning outcomes of class This classroom action research was designed in 2 cycles. Each cycle is carried out in 4 stages, namely planning, implementation, observation and reflection. The competency standards in the learning improvement plan for cycle 1 and cycle 2 are analyzing the origins of the ancestors of the Indonesian nation, the distribution of ancient humans and the lifestyle of pre-literate humans. The indicator is that students draw a map of the distribution of the ancestors of the Indonesian people. The results of classroom action research show that the use of the Picture and Picture cooperative learning model can improve the learning outcomes of class In cycle 2, 35 students (97%) completed it. The average student learning outcome increased from previously 68 in cycle 1, after cycle 2 it increased to 85. Based on the research results obtained, teachers in history learning always provide learning motivation to students, use video media, create effective learning, and use learning models which is fun, so you can be active.